COMPANY VALUE ANALYSIS BASED ON INTELLECTUAL CAPITAL MEDIATED BY FINANCIAL PERFORMANCE STUDY ON LQ 45 COMPANIES IN INDONESIA STOCK EXCHANGE 2015-2019 PERIOD - Puja Firmasari; Rike Setiawati; Fitriati Fitriati (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
Price book value is an indicator of company value that is usually used as an assessment by investors in investing.This study aims to obtain the results of the study of the influence of Intellectual capital on firm value with indicators of value added intellectual capital (VAIC) and financial performance as intervening variables and size, age and leverage as controllers in LQ 45 companies listed on the Indonesian Stock Exchange (IDX). The method used is purposive sampling resulting in a sample of 29 companies. Data analysis using Partial Least Square (PLS) tool. The results show that the influence of intellectual capital on firm value is not directly but fully mediated by financial performance. The financial performance generated through the proper management of intellectual capital is a major concern for investors in assessing the company. Keywords: Intellectual capital, firm value, financial performance